Implementation of ISO 9001:2015 in e-Learning services in higher education - Gunadi, Mochamad Rizal Fikri; Dewi, Laksmi (Inovasi Kurikulum, 2023)
Needs for using a Learning Management System (LMS) in curriculum development in higher education is increasing, including what has happened at the Bandung Institute of Technology. LMS is not only a complementary medium but also a substitute medium for the learning system during the COVID-19 pandemic. This study aims to determine the process of implementing ISO 9001: 2015 in online learning services at the Directorate of Education Development and assess risk mitigation in overcoming obstacles to the curriculum management process. This research was carried out based on the urgency of the management process in curriculum development to support the achievement of curriculum objectives. The method used in this research is qualitative with a descriptive approach. The findings from this study indicate that the Directorate of Educational Development at the Bandung Institute of Technology has implemented ISO 9001:2015 properly, which means it has carried out its duties according to the applicable rules and regulations. Implementing the LMS at the Bandung Institute of Technology applies several criteria related to the Quality Management System (QMS), which is supported by the PDCA (Plan-Do-Check-Act) process and cycle model so that an organization can achieve the desired results. AbstrakKebutuhan akan pemanfaatan Learning Management System (LMS) dalam pengembangan kurikulum di pendidikan tinggi semakin tinggi, termasuk yang terjadi di Institut Teknologi Bandung. LMS tidak hanya sebagai media komplementer, akan tetapi juga sebagai media substitusi sistem pembelajaran di masa pandemi Covid-19. Penelitian ini bertujuan untuk mengetahui proses penerapan ISO 9001:2015 dalam layanan pembelajaran daring di Direktorat Pengembangan Pendidikan, serta mengetahui mitigasi resiko dalam mengatasi kendala pada proses manajemen kurikulum. Penelitian ini dilaksanakan berdasarkan urgensi proses manajemen dalam pengembangan kurikulum untuk mendukung ketercapaian tujuan kurikulum. Metode yang dilakukan dalam penelitian ini adalah kualitatif dengan pendekatan deskriptif. Hasil temuan yang diperoleh dari penelitian ini menunjukkan bahwa Direktorat Pengembangan Pendidikan di Institut Teknologi Bandung telah mengimplementasikan ISO 9001:2015 dengan baik, dan artinya telah menjalani tupoksinya sesuai aturan dan perundang-undangan yang berlaku. Pelaksanaan LMS di Institut Teknologi Bandung menerapkan beberapa kriterai terkait Sistem Manajemen Mutu (SMM) yang didukung oleh model proses dan siklus PDCA (Plan-Do-Check-Act) sehingga sebuah organisasi dapat mencapai hasil yang diinginkan.Kata Kunci: ISO 9001:2015; learning management system; manajemen kurikulum; pembelajaran daring